Políticas educacionais de enfrentamento às situações de violência escolar: Uma análise da atuação do Comitê de Mediação de Conflitos de uma escola da rede pública estadual de educação do Piauí - OLIVEIRA, Clarice Alves de (2023)
The present dissertation, has as its object of study Educational policies to face to situations of violence at the school, of the state public education network of Piauí, and brings the following research problem: what are the impacts of the policy to confront situations of school violence of the state public education network of Piauí, based on the performance of the Conflict Mediation Committee of the school? In this way, it has as its general objective: To analyze the impacts of the policy to confront situations of school violence in the state public education network of Piauí, based on the performance of the Conflict Mediation Committee of the School, located in - Piauí. And as specific objectives: to discuss the state policy for confronting situations of School Violence, demonstrating the impact of the Conflict Mediation Committee; to characterize the main types of violence that occur within the school and the profile of the subjects involved in them, based on the database with records of occurrences related to conflicts and/or infractions produced in that space; identify whether the principles and guidelines that support conflict mediation and restorative practices are included in the school’s Pedagogical Project (PP); describe how the Conflict Mediation Committee of the referred School is constituted and how it develops its attributions; propose a training course for teachers and other education professionals at the school, aimed at dealing with situations of school violence. The methodological perspective adopted was that of a qualitative approach, using document analysis as data collection instruments – Political Pedagogical Project of the school, Internal Regulations, Document of Creation of the Mediation Committee, statistical data from the atlas of violence of the year 2021, data statistics from the School Policing Company (CIPE) in the years 2014 to 2022, the semi-structured interview and bibliographic review. The theoretical basis was based on the authors: Freire (1996), Abramovay and Rua (2002), Charlot (2002), Bourdieu (2014), among others. As a final product of the research, we developed a teacher training course aimed at facing situations of school violence, which will be developed in a Virtual Learning Environment (AVA), aimed at facing situations of school violence, through the mediation of conflicts. The results indicate that: a) the state policy for combating situations of school violence comes from the legal 18po , but over the years it has gained space in the school environment and appears as na alternative means of resolving conflicts that arise at school, thus favoring , the culture of peace; b) there is no database, at the school investigated, with records of the main types of violence that occur within the school and the profile of the subjects involved in them; c) the PP does not clearly and explicitly address conflict mediation; d) the committee is made 18po f twelve people, but some members need to understand their roles before the school; e) the educational policy, through the mediation committee, has not yet been effectively established.